Aedes albopictus in an area of Misiones, Argentina Aedes albopictus en un área de Misiones, Argentina - Nicolás Schweigmann; Darío Vezzani; Pablo Orellano; Jorge Kuruc; Rolando Boffi (Universidade de São Paulo, 2004)
Until early 1998 the presence of Aedes albopictus had never been detected in Argentina. During April of the same year, few individuals of this species were recorded in 33 breeding sites found in 25 out of 161 inspected houses in the city of Eldorado, Province of Misiones. The homogeneous spatial distribution of the proliferation foci suggests the existence of a generalized infestation in this locality during the study period. La presencia de Aedes albopictus en Argentina no había sido detectada hasta comienzos de 1998. En abril de ese mismo año se registraron 33 criaderos, con pocos ejemplares en cada uno, en 25 de las 161 viviendas inspeccionadas en la ciudad de Eldorado, Provincia de Misiones. La distribución espacial homogénea de los focos de proliferación detectados durante el período de estudio sugiere la existencia de una infestación generalizada en esta localidad.